2017
DOI: 10.1016/j.abb.2017.10.018
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic and structural characterization of a cis -3-Chloroacrylic acid dehalogenase homologue in Pseudomonas sp. UW4: A potential step between subgroups in the tautomerase superfamily

Abstract: A Pseudomonas sp. UW4_01740 (designated Ps01740) protein of unknown function was identified as similar to 4-oxalocrotonate tautomerase (4-OT)-like and cis-3-chloroacrylic acid dehalogenase (cis-CaaD)-like subgroups of the tautomerase superfamily (TSF). Ps01740 lacks only Tyr-103 of the amino acids critical for cis-CaaD activity (Pro-1, His-28, Arg-70, Arg-73, Tyr-103, Glu-114). As Ps01740 may represent an important variant of these enzymes, its kinetic and structural properties have been determined. Ps01740 sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 9 publications
(25 citation statements)
references
References 41 publications
0
25
0
Order By: Relevance
“…The positioning of these sequences in the tree, however, suggests that some of them may be good targets for structural characterization that might help to fill out the similarity path in more detail. As a case in point, the identification of Linker 1 led to our targeting of that protein for structural characterization (PDB ID: 5UIF ) ( 57 ), allowing us to include it in the structure-guided alignment shown in Fig. 5 .…”
Section: Resultsmentioning
confidence: 99%
“…The positioning of these sequences in the tree, however, suggests that some of them may be good targets for structural characterization that might help to fill out the similarity path in more detail. As a case in point, the identification of Linker 1 led to our targeting of that protein for structural characterization (PDB ID: 5UIF ) ( 57 ), allowing us to include it in the structure-guided alignment shown in Fig. 5 .…”
Section: Resultsmentioning
confidence: 99%
“…Previously Zhang et al ( 2017 ) identified conserved residues in the superfamily that relate to DNA binding within the photolyase, defining which substrate is recognised and repaired by the photolyase (Table 1 and Fig. 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…The gene encoding fused 4-OT from Burkholderia lata (ATCC 17760, UniProt accession: Q392K7) (designated "fused 4-OT") was codon-optimized for expression in E. coli, synthesized, and cloned into the expression vectors pJ411 (pJ411-F4-OT) by DNA2.0, Inc., now ATUM (Newark, CA). 19…”
Section: Bacterial Strains Plasmids and Growth Conditionsmentioning
confidence: 99%